Hubungan Kohesivitas Kelompok dengan Kecemasan Kompetitif pada Mahasiswa yang Bergabung dalam Organisasi Olahraga di Jakarta - Khoirunnisa, Syaffa Aulia; Claudia, Cindi; Wijaya, Lydia Suliyanto; Subroto, Untung (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Sports teams in facing a match are often faced with the pressure to win, this can trigger competitive anxiety in its members. Group Cohesion is a state of group members who are compact and uphold the value of solidarity. While competitive anxiety is a negative emotional reaction in athletes that arises when their self-esteem is threatened because of a match that is considered difficult. This study aims to determine the relationship between group cohesion and competitive anxiety in students who join sports organizations in Jakarta. The measuring instruments used in this study are the Competitive State Anxiety Inventory-2R (CSAI-2R) and The Group Environment Questionnaire. The sampling technique in this study used Purposive sampling with a total sample of 353 active students of sports organizations in Jakarta. Data processing was carried out using SPSS 25 for Windows. From the results of data processing, it was found that there is a negative relationship between group cohesion and competitive anxiety, namely p value = .000 and r value = -.471. This means that if individuals with high group cohesion then competitive anxiety will be low.  In other words, the stronger the group bond, the less likely members are to feel anxious when facing a match.